Research on correlation between nitrogen compounds, iron and manganese concentrations in drinking water supply systems - Valentukevičiene, Marina; Karczmarczyk, Agnieszka; Jurkienė, Anželika; Grigaitytė, Auksė (Journal of Environmental Engineering and Landscape Management, 2013)
A wide range of material sources potentially contribute to contaminant loads in potable water. The ability of water supply systems to act as emission control barriers to tap water micro pollutants, thereby providing environmental benefits in addition to potable water savings, have not been fully explored. This paper investigates the sources, presence and potential fate of a selection of nitrogen micro pollutants in water supply systems. All of the investigated compounds are listed under the requirements to the quality of water intended for human consumption. Significant water quality changes are identified. A wide range of potential treatment trains are available for water treatment and reuse but treatment efficiency data for nitrogen substances is very limited. Nitrogen substances removal through water treatment is following to be predominantly due to ammonium ions, nitrate and nitrite limited concentrations requirement, with only minor contributions to the water supply network. The majority of conventional water treatment plants periodically supply water with nitrogen compounds residual to the potable water distribution system. Hence, it is important to ensure that other nitrogen sources control options (e.g. pipelines materials, and groundwater sources controls) for potable water supply continue to be pursued, in order that nitrogen compounds emissions from these sources are effectively reduced and/or phased out as required under the demands of the requirements to the quality of water intended for human consumption. The aim of this research was to estimate the correlation between nitrogen compounds, iron and manganese concentrations in drinking water supply pipelines in Vilnius (Lithuania) and Warsaw (Poland). First published online: 11 Oct 2012